Food, work and sleep: Visualising the top food and population centres in Beijing. (May 2019) - Zhou, Jiangping; Yang, Yuling; Zhang, Chun
In contemporary cities, the catering sector is much more than only food and/or eating. On the one hand, it is an important source of income, employment and waste; on the other hand, it provides many opportunities for eating out and social interaction. For a given city, where does the catering sector concentrate the most and how far are people, on average, from this location across hours of a day? Are people, on average, closer to the concentration around the prime dinner time? Taking advantage of open and big data, we geovisualised the answers in the context of Beijing, the capital of China, with a population of 22+ million people. Specifically, the data we used were the 2015 points of interest of Baidu Map (the Chinese counterpart of Google Maps) and 10–16 August 2015 cellular network data for Beijing. The former provide us with the number and location of most if not all restaurants around the local metro-served area (MSA) – that is, areas that are within an 800-metre radius of a metro station. The latter allow us to derive the average number of cellular phone users (as a proxy for the general population, residents and/or employees) by MSA across hours of a day. We depict the top five population/employment/residential centres (quantified by the average number of cellular phone users) at three different times of the day, and the top 10 food centres (measured by the number of restaurants) at the MSA level in Beijing.